PERAN LSM KUSUMA BUANA DALAM PENDAMPINGAN PSK DI DESA BONGAS, INDRAMAYU, JAWA BARAT - Erllyn Nurdiansyah * (Pendidikan Sosiologi FIS UNY, 2012)
LSM Kusuma Buana is one of social institution which focus with countermeasures on sex worker problem in Bongas Vilage, Indramayu, Jawa Barat. The purpose of LSM Kusuma Buana to be effort autonomous for PSK. Purpose of this reseacrh are: 1). To description profil of LSM Kusuma Buana as social institution to handle PSK problem. 2). To description character of LSM Kusuma Buana to handle PSK problem in Bongas, Indramayu, Jawa Barat. This research uses kualitatif research methods. Were used primary and secondary data sources. Technique obtained in this research is descriptive analysis that is the data which obtained in this research presented the analyzed descriptively to get an idea about the facts. Information obtained by using purposive sampling tecnique, that is sampling based on speatic objectives. Informats in this study is the LSM Kusuma Buana, prostitutes and former prostitutes. Data was collected by interview methocl, passive participant observation, documentation and literature studies. To examine the validity of this data source using triangulation techniques source and methods. Techniques which used in analyzing the data is data colection, data reduktion, data presentation, and conclusion. The result showed that: 1). LSM Kusuma Buana as social institusion is the first in Bongas Vilage in assitance prostitutes. 2). The role of LSM Kusuma Buana or Kusuma Bongas as home and friend for sex worker, besides its role as facilitator and catalyst, coach and education, as well as colector of capital. 3). Assistance by LSM Kusuma Buana formed a working group named Kusuma Bongas to empower sex worker by providing mentoring programs, such as community empowerment in the form of revolving capital and education about the worse effect of prostitutions and AIDS, health service and skills activties. Form of empowerement that was given to comecrial sex worker and sex worker make increasingly independent and empowered. 4). Empowerment was given to the prostitutes greated positively by them, because the program can empower prostitutes in Bongas Vilage, Indramayu, Jawa barat. Key words: role of social institutional, assistance program, empowerement